A Comparative Cost Analysis of Antibiotic Treatment for Community Acquired Pneumonia (CAP) in Adult Inpatients at Piggs Peak Government Hospital in Swaziland - Zwane, Sifundo P.; McGee, Shelley-Ann M.; Suleman, Fatima (Frontiers in Public Health, 2018)
Background: Of the different types of pneumonia, community acquired pneumonia (CAP), has been identified as the leading cause of infectious morbidity and mortality in the western and developing countries. To eradicate the bacterial cause of CAP, medical doctors) often tend to prescribe a differing cocktail of medicine which may be costly for the health care system. Aim: To analyze the cost of oral and/or intravenous antibiotic medicine use in different treatment approaches for treating CAP in adult inpatients from the health care system perspective. Settings: This study was undertaken at Piggs Peak Government Hospital, a 220 bed tertiary hospital located in the rural northern Hhohho region of Swaziland. Method: Seventy-one (n = 71) medical records of adult patients, hospitalized and diagnosed with CAP at Piggs Peak Government Hospital from July 2014 to June 2015, were retrieved and entered into the database once confirmed as having met the selection criteria. Only direct antibiotic medicine(s) costs were considered. The total cost per treatment option was calculated by multipling the unit cost of the medicine by the administration frequency and the length of hospital stay. The Kruskal-Wallis test was used to compare the cost difference between more than two treatment options. Results: Medical doctors at Piggs Peak Government Hosptial use a range of antibiotics to treat community acquire pneumonia. Furthermore, doctors prefer using dual antibiotics combination as first line treatment of CAP in adult inpatients. The cost of treating community acquire pneumonia at the hospital ranged from ZAR 70.98 to ZAR 467.60 per adult inpatient admitted into care. A statistically significant difference in the cost of the different treatment approaches used for treating CAP was noted. Conclusion: This cost-exploratory study has highlighted a significant difference in the monetary cost of the differing approaches used for treating CAP at the hospital. It is evident therefore that the use of different treatment approaches in treating CAP significantly influences the cost of CAP treatment. There is therefore need for cost minimization measure to be put in place at the facility.